The Determinants of the Maturity of Corporate Debt Issues - GUEDES, JOSE; OPLER, TIM (Journal of Finance, 1996)
ABSTRACT We document the determinants of the term to maturity of 7,369 bonds and notes issued between 1982 and 1993. Our main finding is that large firms with investment grade credit ratings typically borrow at the short end and at the long end and of the maturity spectrum, while firms with speculative grade credit ratings typically borrow in the middle of the maturity spectrum. This pattern is consistent with the theory that risky firms do not issue short‐term debt in order to avoid inefficient liquidation, but are screened out of the long‐term debt market because of the prospect of risky asset substitution.